Functional Study of Haplotypes in UGT1A1 Promoter to Find a Novel Genetic Variant Leading to Reduced Gene Expression. Issue 3 (June 2015) - Shin, Hee Jung; Kim, Jason Yongha; Cheong, Hyun Sub; Na, Han Sung; Shin, Hyoung Doo; Chung, Myeon Woo
Abstract : Background: Uridine diphosphate glucuronyltransferase 1 family, A1 ( UGT1A1 ) encodes for an enzyme that is a part of glucuronidation pathway, and a number of studies have shown that the promoter polymorphisms of UGT1A1 are associated with various diseases and drug response. In this study, we examined a possible association between UGT1A1 promoter haplotypes and the gene expression level. Methods: To identify promoter haplotype structure population, we directly sequenced the promoter region of UGT1A1 in 192 healthy Korean to identify 10 UGT1A1 promoter single-nucleotide polymorphisms (SNPs). Then, we genotyped the 10 SNPs in additional 192 non-Korean samples comprised of Chinese, Japanese, European American, and African American, and constructed haplotype structures. Furthermore, we conducted luciferase assay for the promoter SNP haplotypes to examine a possible expression change. Results: rs3755319 C— rs2003569 A— rs887829 C— rs8175347 (TA)6 (6.60 ± 0.15) and rs3755319 A— rs2003569 G— rs887829 C– rs8175347 (TA)7 (2.79 ± 0.97) led to significantly lower gene expression when compared with rs3755319 C— rs2003569 G— rs887829 T— rs8175347 (TA)6 (8.28 ± 0.60). Conclusions: Our result suggests that the haplotypes in UGT1A1 promoter region can affect the expression level of the gene and drug metabolism associated with UGT1A1 . Furthermore, in addition to rs8175347, rs3755319 was found to induce lower gene expression of UGT1A1 .